Gambaran Hasil Pemeriksaan Sitologi Serviks Wanita Pekerja Seksual Tidak Langsung pada Hotspot Maredan Kecamatan Tenayan Raya Pekanbaru - Wiwit Ade; Sindy Oktaviani; Amru Sofian (Jurnal Ilmu Kedokteran, 2016)
Cervical cancer is a malignancy of the cervix that can be prevented, but the cause of death of women due to cancer.Cervical cancer is the second most frequent cancer in women in the world. Indirect female sex workers have a higherrisk of cervical cancer. The aim of this research was to figure out description of cervical smear examination in indirectfemale sex workers at hotspot Maredan Tenayan Raya Pekanbaru. Population of this experiment were all indirectfemale sex workers at hotspot Maredan Tenayan Raya Pekanbaru and samples were taken with total sampling method.The result showed that there were 44 people consist 4% diagnosed with HSIL, 25% were diagnosed with LSIL, 30%diagnosed with ASCUS and 41% with negative for intraepithelial lesion or malignancy (Bacterial vaginosis,Trichomonas vaginalis, Candidiasis presents).